2008
DOI: 10.1007/s00572-008-0165-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and temporal dynamics of arbuscular mycorrhizal and dark septate endophytic fungi in a tallgrass prairie ecosystem are minimally affected by nitrogen enrichment

Abstract: Root colonization by arbuscular mycorrhizae (AM) and dark septate endophytic (DSE) fungi in nitrogen amended and unamended mixed tallgrass prairie communities were analyzed monthly over two growing seasons. Roots were stained with Trypan blue and Sudan IV and fungal structures quantified using the modified magnified intersections method. Root length colonized (RLC) by DSE exceeded AM colonization during early part of the growing season. Fungal colonization varied among the years and was greater in 2003 than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 48 publications
5
76
2
1
Order By: Relevance
“…This is similar to studies where a high proportion of dual colonization of AM and DSE fungi in roots of plant species examined have been reported (Massenssini et al 2014;Majewska et al 2015). Our observation of a negative correlation between %RLTC and %RLDTC is in agreement with studies where an inverse relationship between these fungal variables has been reported (Muthukumar et al 2006;Mandyam & Jumpponen 2008;Muthukumar & Tamilselvi 2010). While an interaction between AM and DSE fungal type is expected as they share the same niche within the root system, the nature of the relation between these two fungal types has received far less attention.…”
Section: Relationship Between Am and Dse Fungisupporting
confidence: 92%
“…This is similar to studies where a high proportion of dual colonization of AM and DSE fungi in roots of plant species examined have been reported (Massenssini et al 2014;Majewska et al 2015). Our observation of a negative correlation between %RLTC and %RLDTC is in agreement with studies where an inverse relationship between these fungal variables has been reported (Muthukumar et al 2006;Mandyam & Jumpponen 2008;Muthukumar & Tamilselvi 2010). While an interaction between AM and DSE fungal type is expected as they share the same niche within the root system, the nature of the relation between these two fungal types has received far less attention.…”
Section: Relationship Between Am and Dse Fungisupporting
confidence: 92%
“…13,no. 3 occurrence of DSE and AMF and suggest that it is common in plant roots in nature (Rains et al 2003, Muthukumar et al 2006, SantosGonzalez et al 2007, Mandyam & Jumpponen 2008, Khidir et al 2010, Yang et al 2010) and some of them suggest that colonization of roots can be interfered by non-mycorrhizal endophytes, especially during the hot season which corresponds to the plant growing season when water availability is low and that a competition between both endophytes during colonization could limit the distribution of AM in dry region (Mandyam & Jumpponen 2008, Khidir et al 2010, Yang et al 2010. This relation has not been clarified yet; therefore, further studies are needed for resolving the existing relations between both fungal endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Apple et al (2005) and Cuenca and Lovera (2010) also reported higher mycorrhizal colonization of plant roots in the rainy period in other tropical and desert environments. Most seasonal studies focus on representative plant species rather than the entire plant community as indicated by Mandyam & Jumpponen (2008). In this respect, Sanders and Fitter (1992) suggested that it is essential to follow the seasonal dynamics of AMF in entire plant communities and emphasize that true seasonal patterns can be observed when colonization levels are followed for more than a year.…”
Section: Discussionmentioning
confidence: 99%